THE USE OF SONGS AS A PROMPT IN GENRE-BASED APPROACH IN TEACHING NARRATIVE TEXT - Sintia Hamidah Ilyasa (Journal of English and Education, 2013)
The paper entitled, “The use of songs as a prompt in genre-based approach in teaching Narrative text” aims to examine in what stages of the genre-based approach (GBA) that songs as a prompt can be incorporated in teaching narrative text and to what extent songs as a prompt can help the students in writing narrative text. This study was conducted in a senior high school in Bandung using a case study. The findings of this study show that, songs can be incorporated in every stage in GBA including Building Knowledge of Field, Modeling of Text, Joint Construction, and Independent Construction. Furthermore, the analysis reveals that songs as a prompt can help the students to write narrative text in several aspects, as in helping the students to understand context and social purpose of narrative text, generating ideas, enhancing vocabularies and the use of expressions, and promoting students’ motivation. Regarding this, it is recommended that songs a as a prompt be  incorporated in the GBA to teach narrative text. Keywords:Genre-based Approach, Songs, Writing Prompt, Narrative Text